Miniaturization Smart Antenna Array Design for TD-SCDMA System - Hao Honggang; Hu Wenshuai; Ruan Wei; Chen Wei (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
In view of the development for TD-SCDMA communication system and combine with the miniaturization technology of smart antenna, by using balun feeding structure and consist of splitters and neural networks,  this paper  proposed a four units of dual polarized and a eight units of +45o/-45o polarized antenna array which on the basis of printed dipole antenna. The simulation results show that the isolation of dual-polarized unit between two ports is greater than -26dB, the isolation of 4-unit dual-polarized antenna array between dipole ports are less than -20dB and the 8-unit is less than -18dB. The polarization characteristics and isolation parameter of the proposed antenna has meets the demands of practical applications in the bands of TD-SCDMA communication system and its supplement bands. DOI : http://dx.doi.org/10.11591/telkomnika.v12i2.3752